1989
DOI: 10.1111/j.1471-4159.1989.tb10932.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an Ependymin Precursor from Goldfish Brain

Abstract: Ependymins are thought to be implicated in fundamental processes involved in plasticity of the goldfish CNS. Gas-phase sequencing of purified ependymins beta and gamma revealed that they share the same N-terminal sequence. Each sequence displays microheterogeneities at several positions. Based on the protein sequences obtained, we constructed synthetic oligonucleotides and used them as hybridization probes for screening cDNA libraries of goldfish brain. In this article we describe the full-length sequence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Several N-glycosylation variants of ependymin have been identified, and an important role appears to be the binding of calcium via N-linked sialic acid residues (Konigstorfer et al, 1989;Ganss and Hoffmann, 1993;Hoffman, 1994). Calcium binding activates functionally significant conformational transitions of the ependymin glycoproteins, and it has been suggested that ependymin plays an important role in calcium homeostasis in the brain (Shashoua, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Several N-glycosylation variants of ependymin have been identified, and an important role appears to be the binding of calcium via N-linked sialic acid residues (Konigstorfer et al, 1989;Ganss and Hoffmann, 1993;Hoffman, 1994). Calcium binding activates functionally significant conformational transitions of the ependymin glycoproteins, and it has been suggested that ependymin plays an important role in calcium homeostasis in the brain (Shashoua, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…EPN is secreted by meningeal cells [13]. It has two glycoforms (37 kDa and 32 kDa) and is an important glycoprotein in the cerebrospinal £uid of teleost ¢sh [14]. A bound form of EPN has been identi¢ed in the extracellular matrix of the cerebral blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…A study on the polymerization of ependymins led also to a speculation on the function of ependymins for neural plasticity (Shashoua, 1991). From the first molecular characterization of goldfish ependymins it was tempting to speculate that negatively charged clusters may act as Ca''-binding sites (Konigstorfer et al, 1989a), because no other consensus motifs were detectable. Remarkably, these clusters are not strictly conserved in ependymins from various orders of teleost fish (Miiller-Schmid et al, 1992.…”
mentioning
confidence: 99%